Compressive Strength and Porosity Characteristics of Geopolymer Concrete Containing Used Tyre as Artificial Aggregate - ABDUL HALIM, NUR ELLYA NAJWA; Kusbiantoro, Andri; Ismail , Amalina Hanani (Progress in Engineering Application and Technology, 2025)
The accumulation of waste rubber, particularly from discarded tyres, poses a serious environmental challenge. Its non-biodegradable nature contributes to pollution and disrupts natural habitats. Current mitigation methods, including incineration and landfilling, have significant limitations such as greenhouse gas emissions and the need for extensive land use. To address this issue, utilizing waste rubber as a replacement material in geopolymer concrete offers a promising and innovative solution. This study focused on assessing the feasibility of incorporating crumb rubber as a partial replacement for fine aggregates in geopolymer concrete. The primary objectives were to evaluate the workability, density, and compressive strength of geopolymer concrete containing different proportions of waste rubber from 0-40 %. The crumb rubber, with particle sizes ranging from 1 millimeter to 5 millimeters, was sourced from Parit Sulong, Malaysia, while fly ash from the Manjung Coal-Based Thermal Power Plant was used as the main binder component. Laboratory tests conducted included the Slump Test, Density, Compressive Strength, and Elevated Temperature tests on cube specimens measuring 100 millimeters by 100 millimeters by 100 millimeters after curing periods of 7, 28, and 56 days. The results showed that increasing rubber content improved the workability of the concrete due to enhanced flowability. However, this improvement was accompanied by reductions in both density and compressive strength. While the reduced strength limits the suitability of rubberized concrete for structural applications, its lightweight characteristics make it a viable option for non-structural uses such as lightweight or waterproof materials. This study highlights the potential of integrating waste rubber into sustainable construction practices and emphasizes the importance of further research to optimize the balance between performance and environmental benefits.